Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates for the synthesis of various 6-Oxo nicotinic acid esters - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2019)
Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates via aza-Michael/C-H activation sequence for the synthesis of various 6-oxo nicotinic acid esters is described. The regioselectivity of the protocol has been confirmed by performing silver mediated protodecarboxylation of the corresponding 6-oxo nicotinic acid to furnish 2-pyridone. The developed protocol is copper or silver salt-free and uses inexpensive, safe, and environmentally benign peroxide-based ``oxone'' as the sole oxidant. A redox-neutral version of the protocol is also demonstrated.